STRATEGI PEMBERDAYAAN KEWIRAUSAHAAN MANTAN BURUH MIGRAN PEREMPUAN DI KABUPATEN KEBUMEN - Fitra, Joko; Rizana, Dani (Fokus Bisnis : Media Pengkajian Manajemen dan Akuntansi, 2019)
This study examines the entrepreneurial empowerment strategy of former female migrant workers who are members of the Village community concerned with Migrant Workers. After returning from work abroad, former female migrant workers again experienced an economic downturn, making it difficult to meet basic family needs. This study aims to determine the economic conditions of former female migrant workers after returning, strategies for fulfilling post-return life needs, and entrepreneurial empowerment strategies carried out by various institutions. This research approach uses a descriptive qualitative approach. Data collection techniques using observation techniques, in-depth interview techniques, and library studies and documentation. Taking informants is done by using informant techniques aimed at. Data analysis used the Miles and Huberman analysis model which consisted of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the entrepreneurial empowerment process of former female migrant workers was carried out because there were indications of weakening economic conditions after stopping work abroad. The goal of empowering former migrant workers is to alleviate economic weakness because it is seen that it still has the potential to be able to regain power in meeting economic needs. The empowerment process carried out by cross institutions is well integrated, where each institution coordinates with each other to complement each other's empowerment programs. The synergy of entrepreneurial empowerment carried out on former female migrant workers in Kebumen District has resulted in improved capabilities such as operating business activities, completing business licenses, increasing production capacity, expanding market reach, networking with other communities, increasing turnover and profits, and continuously being encouraged to develop.Keywords: Empowerment, Former Female Migrant Workers, Entrepreneurship